PROSPECTS OF MANUFACTURE AND USE OF COCONUT DRINK IN CREAM TECHNOLOGY FOR RESTAURANT ESTABLISHMENTS - Пенкальськая, Мария; Фурманова, Юлия; Павлюченко, Елена (SWorldJournal, 2020)
The work is devoted to solving a topical problem - the use of vegetable raw materials in the technology of lactose-free beverages as an alternative to cow's milk and the prospects of their use in the technology of dessert products for restaurants.The art